A Contribution to the Study of the tekenu and its Role in Egyptian Funerary Ritual - Delgado, Jose M. Serrano (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
The tekenu is a recurrent element in Egyptian funerary rituals which is not completely understood and, therefore, still raises several questions. The aim of this article is to reassert the human aspect of the tekenu and his role as officiant or ritualist. This study is based on a revision of known sources and incorporates new documents, mainly from the TT 295 and TT 11. In this role of officiant or ritualist, the tekenu participates in several episodes of the funeral ceremony, particularly in a ritual of dormition with a close analogy in the Opening of the Mouth.